The challenge of teaching and learning signed interpretation in times of coronavirus - González-Montesino, Rayco H. (Journal of Learning Styles, 2020)
The pandemic caused by COVID-19 has challenged governments and health systems around the world. At the educational level, there has been a widespread decision to close schools and suspend all face-to-face activity, encouraging teachers and students to continue using distance and online modalities. At Spanish universities, this transition to virtual space was practically instantaneous. However, this urgent adaptation has generated concern as to whether university students will achieve the competences established in the different degrees. This qualitative study presents the SWOT analysis made by a group of students on the adaptation to remote teaching of a sign language interpretation subject. The results show as the main weakness the lack of teacher-discent co-presence and what this implies for the acquisition of competences, while depending on the access and use of technology is perceived as a threat. The development of specific teaching materials and the predisposition of the teacher are strengths of this educational experience, which has made it clear that, in the opinion of the students, learning to interpret sign language online is a viable alternative.
Keywords: Coronavirus; COVID-19; Online Learning; Sign Language; Analysis; Interpreting SWOT Analize